(untitled) (Journal of Informatics Education and Research, 2025)
This paper attempts to show the losing metamorphosis of female identity into a tag of social roles and labels, turning women into “adjectives” in George Bernard Shaw’s Mrs Warren’s Profession and Mohan Rakesh’s Ashad Ka Ek Din. The study explores the representation of the systematizing oppression and objectification of women, situating both texts in distinctly related cultures and historical frames from a comparative perspective. The protagonists—Mrs. Warren and Vivie in the context of Victorian English life, and Mallika in ancient yet modernistically interpreted India—are early practitioners, who, like the protagonists of both novels, work within a male-dominated structures that inhibit their autonomy, upend their self- worth (as they know it to be) and generally subvert their sense of self.